Modern technologies in the development of reading and writing skills - Muhammadjonova, Nilufar (The Lingua Spectrum, 2025)
This graduation thesis examines the role, importance and scientific support of modern technology in the process of teaching reading and writing. In comparison with traditional methods of teaching, it analyzes what innovative solutions the new technology brings to the educational process, the contribution of teaching to the acquisition of knowledge. The main goal of the work is to determine the impact of the technology used in teaching reading and writing on the pedagogical process, what facilities are available for the teacher and students of reading. Research information and communication technologies, multimedia resources, interactive platforms and downloading from electronic textbooks are studied. Analysis of how software, virtual and student learning and AR) technologies can help students learn and actively participate in the learning process. Adoption of specific features in the process - mastery of reviewing materials, development of creative and critical thinking skills, preparation of materials with independent vision. In this connection, the introduction of modern technologies depends on the production of the educational system, for example, gaining experience with insufficient technical capabilities. The role of work technologies in the process of teaching reading and writing, the use of modern technologies in the control of the literacy of students is taken into account. Practical recommendations on the effective use of communication technologies in the educational process have been developed, with specific directions for their size.